A Simple Self-Balancing Robot For Educational Purposes - Ahmad Nizam, Noorshaheefa; JAFFERI, NOORMAZIAH (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This paper presents the design, development, and implementation of a simple self-balancing robot for educational purposes. The aim of this project is to introduce fundamental concepts of robotics, control systems, and programming to students and enthusiasts in a hands-on, accessible manner. The self-balancing robot comprises basic components including an Arduino microcontroller, inertial measurement unit (IMU), motor drivers, and DC motors. The control algorithm integrates sensor data from the IMU to maintain the robot's balance by adjusting motor speeds in real-time. The design process emphasizes simplicity and affordability, utilizing off-the-shelf components to ensure ease of assembly and accessibility. Additionally, the programming logic is structured to facilitate understanding for beginners, allowing for modifications and enhancements as learners progress in their knowledge. In conclusion, this simple self-balancing robot serves as an educational tool to introduce robotics principles, control theory, and programming concepts in an engaging and accessible manner, fostering curiosity and understanding among learners in the field of robotics and automation.